Non-Animal Methods: An Epochal Etichal and Scientific Turning Point? (BioLaw Journal - Rivista di BioDiritto, 2026)
The new millennium has seen, in Great Britain, in the United States and, albeit with greater fluctuations and resistance, in the European Union, institutions and companies invest significant amounts in the emerging sector of the technologies alternative to animal testing, generally grouped under the acronyms NAT (Non-Animal Technologies) or NAM (New Approach Methodologies). Innovative techniques that, in addition to reducing the number of animals forced into captivity, suffering and early death for research purposes, are, in the areas in which they have been applied so far, more reliable, rapid and economical than traditional animal testing. The article offers an overview of the developments that have characterized this sector, in the last two decades, and of their current orientations, proposing, in the final section, some reflections on their scientific, social and ethical relevance.
Keywords: animal testing; Non-Animal Technologies; “in vitro”; “in silico”; organoids; organ-on-a-chip; omics technologies